Santri, Misi Politik dan Perumusan Kebijakan Publik di Kabupaten Jember - Muhaimin Muhaimin; Abd Wahab (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2019)
This article aims to describe some questioned points of political roles of santris seem like; the understanding of social transformation and its regulatory process inside government, how they articulated, participated, and sounded their ambitions become a regulation, then the last is how they build the dialog beyond political and social interests between both process. This research took places in Jember Region. One of small-town in East Java which Santri and Nahdlatul Ulama’ had significant roles, weather in social and political conducts. In the end, this article conclude that; first there are tree missions how santri articulate their understanding of Islamic point of view to become substance regulation aspect, in term; conservatism, progressivism, and moderate. Second, modes of participations are based on al Maslahah al Ummah (common good) as main orientation, were not just becoming intellectual mouth-pieces of government. Third, ideologically, the relation and dialectical tension beyond santri and government were criticism. It means santris were becoming the critical partner of government to formulate the public policy.